PENGARUH DOSIS PUPUK NITROGEN, FOSFOR, DAN KALIUM TERHADAP PRODUKSI BENIH PADI VARIETAS MAYANG PADA TIGA LOKASI DI LAMPUNG UTARA - Ridwansyah, Budi; Basoeki, Tjipto R.; Timotiwu, Paul B.; Agustiansyah, Agustiansyah (JURNAL AGROTROPIKA, 2010)
Fertilizer is one of the ways to improve cultural techniques for producing high quality of seed with high early vigor. The objectitive of N, P,and K nutrient in balanced quantity can improve productivity and quality of seed rice. His research was to know response of three doses of N, P, and K on growth, production, and quality of seed rice of Mayang variety on three locations on North Lampung, and see interaction of both factors. Treatment arrangement was factorial by randomized complete block design with three replications. Sub factor is fertilizer (P); there are low fertilizer dose (P1) is farmer fertilizer dose consist 200 kg/ha urea and 50 kg NPK/ha; middle fertilizer dose (P2) is recommended government dose consist 250 kg/ha urea, 100 kg Sp 18/ha, and 100 kg/ha KCl; and high dose (P3) is recommended dose for seed production consist 300 kg/ha urea, 150 kg/ha SP 18, and 150 kg/ha KCl. Mains factor is location, there are Ciamis-Sungkai Utara, Wonomarto-Kotabumi Utara, and Semuli Jaya-Abung Semuli. Homogenity of varian each treatment analyzed by Bartlett test and to see eaded model by Tukey test. If all assumption are completely, data will be continue analyzed with BNJ test at level 5%. Result of research showed that high dose fertilizer is can give growth and seed production better than low dose fertilizer, but nonsignificant with middle dose. The best location for seed production is Semuli and than Wonomarto, and Ciamis in the last position, but nothing interaction between different of dose and location.Key words: rice, Mayang viability, fertilizer